American Government: Balancing democracy and rights - Landy, Marc (McGraw Hill Higher Education, 2003)
The essential story of American politics and government is the relationship between liberalism and democracy. American Government demonstrates that the tensions and complementarities between liberalism and democracy are crucial for understanding each and all of the central governing institutions and political elements of American public life. The book deals extensively with contemporary political developments, and it provides all the information and breadth of coverage required of an introductory text. But it does so in a manner that highlights the lessons of history and the drama of politics. It shows that the crucial features of the American political system were established through difficult decisions made under enormous pressure and often agonizing, even bloody, conflict. By placing such critical choices in specific times throughout American history, it is the first textbook to adopt an American Political Development approach.